Optimization of ozone decomposition time and its effect on physicochemical and bacteriological quality of table water - Nwaiwu, Ogueri (Array, 2019)
Ozone is widely used in water disinfection and the concentration needed for the effective microbial elimination depends on the water source. In many bottled water producing industries, products containing ozone are quarantined after application to allow decomposition into diatomic oxygen molecules and oxygen atoms in order to eliminate any toxic effect. A process optimization was carried out to determine the ozone decomposition time in a table water producing factory in southern Nigeria. To this end, bottled water products injected with the ozone were collected from a bottling line immediately after production and monitored for ozone decomposition. Parameters like total dissolved solids, temperature and pH were determined and bacteriological analyses for total bacteria count and presence of Pseudomonas and coliforms were carried out. It was found that the ozone half-life was under 30 minutes and was no longer detectable after two and a half hours. For all analyzed stored products, the pH was in the range of 7.0-7.06, while the temperature was between 23 and 25 °C. The total dissolved solids ranged from 0.05 to 0.09 mg/mL, and there was no significant difference (p>0.05) for the bottled products stored for 24 or 48 hours after the production. No bacteria weredetected. The shorter quarantine period allows quicker distribution and highlights the importance of ozone decomposition testing for the process optimization, especially if equipment or water source change over time.